Pengelolaan Kesehatan Reproduksi Sebagai Upaya Pembangunan Kesehatan Sumber Daya Manusia (SDM) - Pintam Ayu Yastirin; Wahyu Utami Ekasari; Nurulistyawan Tri Purnanto (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
Background: Health development aims to increase awareness, willingness and ability to live healthy for everyone in order to realize the highest degree of public health as an investment for the development of socially and economically productive human resources. Grobogan Regency is one of the districts with the highest cases related to maternal and child health. Based on 2019 data, there were 36 cases of maternal death while infant mortality cases were 13.2 / 1000 KH). Here there is a need for strong efforts to improve health, especially reproductive health nationally. Purpose: To improve reproductive health in the adolescent age group and pregnant women. Method: This activity was carried out in Kuripan Village with 12 adolescents and 8 pregnant women as participants. The implementation of the activity was assisted by 4 students. The method of implementing community service uses a descriptive survey with implementation techniques through anamnesis, physical examination, documentation study, and observation. Results: There were 20 participants (100%), subjective data found that teenagers did not know about the importance of adolescent reproductive health, and through objective data collection, pregnant women with anemia and fetal position abnormalities were found. The intervention carried out was the provision of adolescent reproductive health counseling and the implementation of pregnancy exercise. Conclusion: The community service activity was attended by 20 participants with activities including subjective data collection including anamnesis, objective data including physical and supporting examinations, problem determination and implementation of interventions, namely counseling and pregnancy exercise.